2021
DOI: 10.1111/jgh.15597
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity as a risk factor for lean non‐alcoholic fatty liver disease in potential living liver donors

Abstract: Background and Aim This study aimed to investigate the relationship between hepatic steatosis (HS) evaluated by biopsy and visceral adiposity assessed by computed tomography in lean living liver donor candidates and to determine the risk factors for lean non‐alcoholic fatty liver disease (NAFLD). Methods This retrospective study included 250 lean (body mass index, < 23 kg/m2) potential living liver donors (mean age, 31.1 ± 8.6 years; 141 men) who had undergone liver biopsy and abdominal computed tomography bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Previous research found that NAFLD patients have more VAT than healthy controls 42 . Similarly, we observed a positive causal relationship between genetically predicted VAT and NAFLD risk.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research found that NAFLD patients have more VAT than healthy controls 42 . Similarly, we observed a positive causal relationship between genetically predicted VAT and NAFLD risk.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding hard outcomes, an analysis of the NHANES III survey showed that, compared to healthy lean subjects, lean patients with NAFLD had a 50% increase in all-cause mortality and over a 2-fold increase in cardiovascular mortality [95]. In this line, individuals with lean NAFLD had a significantly higher atherosclerotic cardiovascular disease (ASCVD) score (defined as an ASCVD risk of >10%), 51.6% vs. 39.8% in obese NAFLD and 25.5% in subjects without NAFLD [30]. Additionally, in a recent meta-analysis from the US, non-obese NAFLD individuals had higher 15-year cumulative all-cause mortality (51.7%) than obese NAFLD (27.2%) and non-NAFLD (20.7%) [8].…”
Section: Other Clinical Outcomesmentioning
confidence: 98%
“…Importantly, in people with expanded visceral adiposity, the contribution of VAT to portal vein FFAs' levels can go up to 50% [29]. Recently, a biopsy-based study including 250 lean, potential living liver donors, the severity of NAFLD was positively correlated with visceral fat accumulation [30].…”
Section: Visceral Fat and Metabolic Dysfunctionmentioning
confidence: 99%
“…A study with 352 participants found a correlation between NAFLD onset and thickness of visceral fats [115] . Francque et al [116] reported a considerable association of visceral obesity with the degree of steatosis.…”
Section: Correlation Of Sarcopenia and Nafldmentioning
confidence: 99%